Ultraviolet assisted fenton oxidation hybrid process for treating recalcitrant textile wastewater / Archina Buthiyappan - Archina, Buthiyappan (2016)
It is estimated that about 17-20% of freshwater pollution worldwide occurs due to untreated textile wastewater discharges. Advanced oxidation processes (AOPs) are more suitable for treating textile wastewaters contaminated with recalcitrant organic compounds. In this regard, Batik Industry in Malaysia, which are commonly operated in a cottage set-up, are in dire need for stand alone, simple and cheaper treatment system based on AOPs. Among AOPs, the Fenton process is commonly used for degradation of organic pollutants. However operating cost due to high chemical consumption and excessive sludge production limits the large-scale application. In order to improve degradation performance and reagent utilization efficiency, as well as reduce treatment cost and sludge, ultraviolet radiated integrated Fenton oxidation hybrid process (UV-Fenton) was investigated for Batik wastewater treatment. In this study, the treatment efficiencies of Fenton process and UV-Fenton hybrid process was evaluated using a laboratory sized experimental setup for batik industry wastewater equipped with a low-pressure UV lamp with or without irradiation. The operating parameters evaluated are initial pH of the wastewater, retention time, mass ratios of H2O2:COD and H2O2:Fe2+ and UV radiation intensity. Response surface methodology was used to design the experiment and optimize the operating parameters. The efficiency was evaluated based on COD, TOC and color removals. The kinetic model was also established in this study. Additionally, SEM/EDX and particle size analyses were conducted to characterize the generated sludge. The intermediate species formed during the reaction were observed through GC/MS, FTIR and HPLC analyses. Studies on the treatment efficiencies of direct photolysis, UV/H2O2, UV/Fe2+ coagulation and Fe2+ coagulation were also evaluated as a comparison.